Active recovery intervals restore initial performance after repeated sprints in swimming - Kostoulas, I. D.; Toubekis, A. G.; Paxinos, T.; Volaklis, K.; Tokmakidis, S. P. (European Journal of Sport Science, 2018)
The purpose of this study was to examine the effects of active recovery (AR) and passive recovery (PR) using short (2-min) and long (4-min) intervals on swimming performance. Twelve male competitive swimmers completed a progressively increasing speed test of 7 × 200-m swimming repetitions to locate the speed before the onset of curvilinear increase in blood lactate concentration (LT1). Subsequently, performance time of 6 × 50-m sprints was recorded during four different conditions: (i) 2-min PR (PR-2), (ii) 4-min PR (PR-4), (iii) 2-min AR (AR-2) and (iv) 4-min AR (AR-4) intervals. Blood lactate concentration was measured before the first and after the last 50-m repetition. AR was applied at an intensity corresponding to LT1. Performance as indicated by the time needed to complete 6 × 50-m sprints was impaired after AR-4 compared to PR-4 (AR-4: 28.65 ± 1.04, PR-4: 28.17 ± 0.72 s; mean% difference: MD% ±s; ±90% confidence limits: 90%CL, 1.71 ± 3.01%; ±1.43%, p = .01) but was not different between AR-2 compared to PR-2 conditions (AR-2: 28.68 ± 0.85, PR-2: 28.69 ± 0.82 s; MD%: 0.03 ± 1.61%; 90%CL ± 0.77%, p = .99). Performance in sprint-6 was improved after AR compared to PR independent of interval duration (AR: 28.55 ± 0.81, PR: 29.01 ± 1.03 s; MD%: 1.52 ± 2.61%; 90%CL ± 1.2%; p = .03). Blood lactate concentration was lower after AR-4 compared to PR-4 but did not differ between AR-2 and PR-2 conditions. In conclusion, AR impaired performance after a 4-min but not after a 2-min interval. A better performance during sprint-6 after AR could be attributed to a faster metabolic recovery or anticipatory regulatory mechanisms towards the end of the series especially when adequate 4-min active recovery interval is applied